Sungai Nipah Beach Nauctical Inspection In Subdistrict of IV Jurai Sout Coastal Regency West Sumatera Province - Trivianti, Melsya; Bathara, Lamun; Yulinda, Eni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was condicted in Sungai Nipah Beach Subdistrict of IV Jurai South Coastal Regency West Sumtaera Province. This research aim to know the general representation potential of Sungai Nipah Beach if it made to be a tour destination area. The method of this research is Survey method. This object for this research is Sungai Nipah Beach and local resident, fisherman, and government for the respondent.The potential of Sungai Nipah Beach possession is guite huge to be made for a tour destination area in west Sumatera Province. Based on the water ecological and geografical the very potential site of the beach to develop is diving activity, Banana boad recreation, Vositing Keong Island and to see the beautiful view of the beach. And accordingly to Sungai Nipah Beach revenue as the tourist destination area, the society reception to the tour potential make the local society (93,34%), tourist (100%), Fisherman (84,78%), doer labor (86,67%) and Stakeholder (100%) precentage agree to be made tour destination area. Government contribution for the beach development by far is not found yet, because of the unpretentious management of the local resident wether this beach is already included to the tour object destination in south coastal regency.Keyword:Potential, NaucticalEcotourism, andIdentification